Geochemistry of the Topuk Pluton associated with the Kozbudaklar W-skarn deposit (Western Anatolia, Turkey): Implication for crystallization conditions. (June 2017) - Orhan, Ayşe; Demirbilek, Mehmet; Mutlu, Halim
Abstract: The Kozbudaklar scheelite-bearing skarn deposit in the Tavşanlı Zone, western Turkey, occurs at the contact between Eocene Topuk pluton and Triassic İnönü marble of calcic character. The Topuk pluton is medium-coarse grained, granodiorite in composition and has a hypidiomorphic equigranular texture. The host rock contains mafic microgranular enclaves (MME) of monzodiorite–monzogabbro composition and is interrupted by porphyritic granodiorite and granite-aplite vein rocks. The pluton is calk-alkaline, metaluminous and composed of I-type melt character. δ 18 O and δD compositions of silicate minerals from granodioritic host rock are 5.9–10.6‰ and −77.0 to −71.4‰ and conformable with the range of unaltered I-type granites. Trace element contents indicate that pluton is crystallized from mantle-derived magma interacted with continental crust in a volcanic arc or subduction related setting. Major and trace element concentrations of Topuk pluton are quite consistent with geochemical patterns of Cu-skarn granitoids. Results of mineral chemistry analysis of the pluton yield that plagioclases are of oligoclase–andesine, amphiboles are of magnesio-hornblende and biotites are of ferro-magnesian composition. Amphiboles and biotites of granodioritic host rock are represented by calc-alkaline, I-type melt composition evolved in a subduction environment. Based on the results of plagioclase–Al in hornblende and amphibole chemistry data from the pluton, two different stages are proposed for the magma crystallization. The first stage was developed in a relatively deeper environment (>15 km) under high pressure (>4 kbar) and low log ƒO2 (>−17.6) conditions which reflect fractional crystallization and magma-mixing depth of basaltic magma and these conditions are not correlated with scheelite mineralization. The second crystallization stage of magma which proceeded at shallow depths (<6 km) was also developed in two separate phases with respect to P-T conditions. The first phase associated with scheelite mineralization is characterized by high temperature (788–854 °C), relatively high pressure (1.20–1.62 kbar), shallow depth (5–6 km) and high log ƒO2 (>−12.9 to −11.0) values are accompanied by high H2 O contents (5.39–6.88 wt.%). High water content of melt gave rise to magma to ascend to shallower depths (4–3 km) and crystallization to proceed under low pressure (∼1.00 kbar), high temperature (751–859 °C) and log ƒO2 (−13.3 to −11.0) conditions with lower water contents (4.55–5.50 wt.%). Highlights: Kozbudaklar W-skarn is consistent with geochemical patterns of Cu-skarn granitoids. Mineral chemistry of Topuk pluton implies multistage crystallization. Physicochemical conditions of skarn are estimated by various thermobarometric models.